Conditional Factors of Political Budget Cycles: Economic Development, Media Pressure, and Political Fragmentation. Issue 4 (2nd October 2018) - Cuadrado-Ballesteros, Beatriz; García-Sánchez, Isabel-María
Abstract: This study clarifies the heterogeneity of results in the political budget cycle (PBC) literature by asking which factors are more likely to produce these cycles. Our findings for a sample of 145 Spanish local governments over the period 2005–2013 suggest that governments tend to behave opportunistically when media pressure is low and political fragmentation is high, but they behave ideologically when media pressure and political concentration increase. Economic development also partially explains the differences among partisan PBCs, although we find opportunistic PBCs in both less and more developed municipalities. These findings support Frey and Schneider's conclusion of no simultaneity of opportunistic and partisan PBCs.